Assessment of Straight and Bend Aluminium Alloy 6061 Pipelines Operating Under High Pressure and Temperature Condition Up to 24 Hours by Using Finite Element Analysis - Hassan, Muhammad Syahiran (IRC, 2021)
Creep is the one of the main problemsfor the pipeline in the oil and gas industry due to high temperature, high pressure, and service for a long time.